Academic Governance of Islamic Higher Education as an Incentive Arena: Integrative Literature Analysis Based on Game Theory - Dinana, Aqimi; Muhammad Syaikhul Basyir; Wirdatul Aini (Indonesian Journal of Action Research, 2025)
Purpose – This study aims to analyze academic governance in Islamic higher education as an incentive arena that shapes the strategic behavior of academic actors. It addresses the problem that formal regulations, accreditation systems, quality standards, and institutional visions do not automatically produce academic practices aligned with quality, integrity, and Islamic values. The main argument is that governance problems should be understood not only as managerial or regulatory issues, but also as problems of incentive design. Design/methods – This study employs an integrative-conceptual literature review. The reviewed literature covers Islamic higher education governance, game theory, principal-agent relations, academic incentives, quality assurance, performance-based policy, and research integrity. The data were analyzed through thematic synthesis by mapping actors, rules of the game, strategic choices, incentives, risks, payoffs, and governance outcomes. Findings – The findings show that Islamic higher education faces tension between performative demands, such as accreditation, publication, academic promotion, reputation, and internationalization, and normative values, such as trustworthiness, scholarly honesty, social responsibility, justice, and public benefit. When incentive structures reward administrative compliance and quantitative outputs more strongly than substantive quality, academic actors tend to choose strategies that are bureaucratically safe but academically weak. This study proposes an incentive-aligned model of Islamic academic governance that makes high-quality, honest, collaborative, and value-based academic behavior the most rational choice. Keyword: academic governance; Islamic higher education; game theory; academic incentives; scholarly integrity.